Intelegensi Tinggi, Prestasi Rendah: Analisis Peran Faktor Non-Kognitif dalam Keberhasilan Belajar Siswa MI/SD - Uci Purnama Sari; Mariza Rahma Via; Anisa .; Adriyanto . (CV. ITTC INDONESIA, 2026)
The phenomenon of Madrasah Ibtidaiyah (MI) or Elementary School (SD) students who have high intelligence but show low learning achievement is a significant problem in the world of basic education. This shows that learning success is not only determined by cognitive abilities, but is also influenced by non-cognitive factors that are often overlooked in the learning process. This study aims to analyze the role of non-cognitive factors in influencing the learning success of MI/SD students who have high intelligence but have not achieved optimal achievement. The research method used is a descriptive qualitative approach through a literature review by examining various relevant scientific journals and books in the period 2015–2024. Data analysis techniques are carried out systematically through the stages of data reduction, categorization, synthesis of findings, and drawing conclusions to find patterns of relationships between intelligence and learning achievement. The results of the study indicate that non-cognitive factors such as learning motivation, self-regulation, self-efficacy, emotional intelligence, and family and school environmental support have a significant role in optimizing students' intelligence potential into learning achievement. This finding confirms that low learning achievement in students with high intelligence is generally caused by weak non-cognitive factors that inhibit active interaction in learning.